Force transmission is a master regulator of mechanical cell competition - Schoenit, Andreas; Monfared, Siavash; Anger, Lucas; Rosse, Carine; Venkatesh, Varun; Balasubramaniam, Lakshmi; Marangoni, Elisabetta; Chavrier, Philippe; Mège, René Marc; Doostmohammadi, Amin; Ladoux, Benoit (Nature Materials, 2025)
Cell competition is a tissue surveillance mechanism for eliminating unwanted cells, being indispensable in development, infection and tumourigenesis. Although studies have established the role of biochemical mechanisms in this process, due to challenges in measuring forces in these systems, how mechanical forces determine the competition outcome remains unclear. Here we report a form of cell competition that is regulated by differences in force transmission capabilities, selecting for cell types with stronger intercellular adhesion. Direct force measurements in ex vivo tissues and different cell lines reveal that there is an increased mechanical activity at the interface between two competing cell types, which can lead to large stress fluctuations resulting in upward forces and cell elimination. We show how a winning cell type endowed with a stronger intercellular adhesion exhibits higher resistance to elimination and benefiting from efficient force transmission to the neighbouring cells. This cell elimination mechanism could have broad implications for keeping the strong force transmission ability for maintaining tissue boundaries and cell invasion pathology.
CRIS-Team Scopus Importer:2025-04-01